KYRGYZSTAN: MENTALITY AND MODERNIZATION - BEYSHEMBAEVA, Anara (CENTRAL ASIA AND THE CAUCASUS, 2004)
There is no need to hold forth about the faults of the republic’s political system—everybody knows that the political, economic and spiritual culture is weak. At the same time, however, one can detect symptoms of political and economic stabilization.1 Here I shall touch upon a more subtle issue that is much harder to grasp: a crisis of Kyrgyz mentality. Is there a crisis? A positive answer invites two other questions: Are there symptoms of the end of the crisis? In which way can the crisis be overcome? In his time, Pitirim Sorokin convincingly described a social crisis as a loss of the vector of mental life by a social-cultural “super-system.” This leads to axiological disintegration and “moral polarization” of public mentality. One can say that in the context of such crisis many personal minds loss their ability, completely or partially, to complete self-realization and adequate self-identity, thus causing a deficit of social subjectivity. At the same time, according to Pitirim Sorokin, deep-cutting mental crises are an inalienable part of the worldwide historical process; in many cases they bring in a new more socially and culturally productive lifestyle. This obviously adds urgency to correct sociological diagnoses and interpretations of the crisis phenomena of our mental life.Mentality is an extremely important component of any socium: as a sociocultural subject man be-longs not so much to the objective world as to the inter-subjective picture of the world painted by mentality. We can a priori presuppose the existence of at least two vectors of Kyrgyz mentality: quietism (rest as an ultimate value: nothing should be sought for, nothing should be rejected) and utopia (of communist,liberal or any other kind). However, disintegration of Kyrgyz society and its metal differentiation are much more complex phenomena and more varied. Throughout the last few years, society has been living amid continuous economic, political, and social reforms caused by a systemic transfer from one socioeconomic structure to another. These fundamental social changes, an interaction among all trends and directions of development cause qualitative ideological shifts; they change personal and ethnic relationships and the nation’s axiological landmarks. As a result, civil society will come into being. The world looks at Kyrgyzstan as a democratic, secular, socially oriented state ruled by law, yet life of common people has not improved. The country’s huge external debt (by late 2002 it was $1,732.3m, according to the National Bank),2 unemployment (over 500,000, according to expert assessment),3 and poverty of the wide popular masses (an average monthly wage, slightly above $30, is one of the CIS lowest)4 do not allow the state to raise the living standards. Economy will deteriorate in the near future, thus making more people poorer. Old-age pensioners (70 percent of them, according to official figures live below the poverty level) and those who depend on the state for survival will suffer most.